Consumption of snakehead fish (channa striata) on postpartum maternal perineal wound healing - Citra Purwanti; Renda Natalina; Riska Marlin (Journal of Health Technology Assessment in Midwifery, 2019)
This study aimed to determine the effect of Snakehead fish consumption on the healing of perineal wounds in postpartum mothers. The method used is quasi experimentof pre-post test control group design. The sample in this study were postpartum mothers in Palembang city who were willing to become respondents. Samples totaled 30 mothers. This research was conducted in the working area of BPM Ellna, BPM Herasdiana and BPM Soraya located in Seberang Ulu I Subdistrict, Seberang Ilir I Subdistrict and Kemuning Subdistrict. The researchers collected data by giving raw Snakehead fish for postpartum mothers as much as 100gr per once, 3 times a day for 10 days. The result is the effect of Snakehead fish consumption (Channa Striata) on postpartum maternal perineal wound healingwhich obtained the results of statistical tests showed obtained Sig (2-tailed) values of 0.000 0.05.